Developing a theory of focal company business sustainability efforts in connection with supply chain stakeholders. Issue 1 (12th February 2018) - Svensson, Göran; Ferro, Carlos; Hogevold, Nils; Padin, Carmen; Sosa Varela, Juan Carlos
Abstract : Purpose: The purpose of this paper is to test the structural properties of a stakeholder research model of focal company business sustainability and the associated consideration of upstream, downstream, market and societal stakeholders. Design/methodology/approach: Based on two industrial business samples in Norway and Spain, partial least squares– structural equation modelling (PLS-SEM) was applied to empirically test a research model consisting of five stakeholder constructs. Findings: The model was tested in Norway and validated in Spain. An analysis of the path coefficients and levels of significance shows that all relationships in the research model were significant and meaningful. Research limitations/implications: This paper develops a model that explains and predicts company considerations of other stakeholders in the business sustainability efforts within supply chains (both upstream and downstream) and also beyond in the market and society. Practical implications: The results of this study can guide companies in structuring, planning and implementing business sustainability in their supply chains, the marketplace and the society. It can also provide a foundation for monitoring and follow-up assessment of corporate decision-making. Originality/value: This study contributes to supply chain management (SCM) and stakeholder theory to establish a framework for business sustainability with respect to company stakeholders in supply chains.